PENGARUH KETERAMPILAN MANAJERIAL KEPALA SEKOLAH DAN IKLIM ORGANISASI SEKOLAH TERHADAP KINERJA GURU SMK NEGERI KELOMPOK TEKNOLOGI INDUSTRI DI KOTA SEMARANG - Sumaryono Sumaryono (JURNAL LITBANG PROVINSI JAWA TENGAH, 2010)
Education is important in society life. Education builds someone’s way of life and thinking. Besides, it creates someone’s development of thinking way. Good and qualified education needs professional and competent education workers, headmasters’ management skill and organization climate. Those have important roles in developing teacher’s performance. This research is formulated into: 1) How far is the effect of headmasters’ management skill to teachers’ performance? 2) How far is the effect of schools’ organization climate to teachers’ performance? 3) How far is the effect of headmasters’ management skill and organization climate to teachers’ performance?. The population were all teachers in State Vocational Schools of Industrial Teachnology Group in Semarang. The sample were 96 people using probability sampling technique. The analysis tools were regression, t test and F test.The result analysis used SPSS program showing the variable of headmaster’s management skill having significant positive impact to teachers’ performance. The significant test result shows the variable significance value of headmasters’ management skill is lower than 0.05; Ho is denied and Ha is accepted. The variable of schools’ organization climate gives positive impact to teachers’ performance. The significance test result shows the variable significance value of schools’ organization climate is lower than 0.05; Ho is denied and Ha is accepted. The variable of headmasters’ management skill and schools’ organization climate give positive impact to teachers’ performance. The significance test result shows that the significance value is lower than 0.05; Ho is denied and Ha is accepted.